Immediate and short-term effects of continuous theta burst transcranial magnetic stimulation over contralesional premotor area on post-stroke spasticity in patients with severe hemiplegia: Study protocol for a randomized controlled trial - Wei, Xiupan; Xia, Nan; Li, Yang-An; Gu, Minghui; Zhang, Tongming; Gao, Wei; Liu, Yali (Frontiers in Neurology, 2022)
Background Post-stroke spasticity is an important complication that greatly affects survivors' functional prognosis and daily activities. Increasing evidence points to aberrant contralesional neuromodulation compensation after brain injury as a possible culprit for increased spasticity in patients with severe stroke. Hyperactivity of the contralesional premotor area (cPMA) was supposed to be highly correlated with this progression. This study aims to demonstrate the immediate and short-term efficacy of continuous theta-burst stimulation (cTBS) targeting cPMA on upper limb spasticity in severe subacute stroke patients. Methods This trial is a single-center, prospective, three-group randomized controlled trial. Forty-five eligible patients will be recruited and randomized into three groups: the sham-cTBS group (sham cTBS targeting contralesional PMA), the cTBS-cM1 group (cTBS targeting contralesional M1), and the cTBS-cPMA group (cTBS targeting contralesional PMA). All subjects will undergo comprehensive rehabilitation and the corresponding cTBS interventions once a day, five times a week for 4 weeks. Clinical scales, neurophysiological examinations, and neuroimaging will be used as evaluation tools in this study. As the primary outcome, clinical performance on muscle spasticity of elbow/wrist flexor/extensors and upper-limb motor function will be evaluated with the modified Ashworth scale and the Fugl-Meyer Assessment of Upper Extremity Scale, respectively. These scale scores will be collected at baseline, after 4 weeks of treatment, and at follow-up. The secondary outcomes were neurophysiological examinations and Neuroimaging. In neurophysiological examinations, motor evoked potentials, startle reflex, and H reflexes will be used to assess the excitability of the subject's motor cortex, reticulospinal pathway, and spinal motor neurons, respectively. Results of them will be recorded before and after the first cTBS treatment, at post-intervention (at 4 weeks), and at follow-up (at 8 weeks). Neuroimaging tests with diffusion tensor imaging for all participants will be evaluated at baseline and after the 4-week treatment. Discussion Based on the latest research progress on post-stroke spasticity, we innovatively propose a new neuromodulation target for improving post-stroke spasticity via cTBS. We expected that cTBS targeting cPMA would have significant immediate and short-term effects on spasticity and related neural pathways. The effect of cTBS-cPMA may be better than that of cTBS via conventional cM1. The results of our study will provide robust support for the application of cTBS neuromodulation in post-stroke spasticity after a severe stroke. Clinical trial registration This trial was registered with chictr.org.cn on June 13, 2022 (protocol version). http://www.chictr.org.cn/showproj.aspx?proj=171759.